Penentuan Awal Bulan Qomariyah dan Permasalahannya di Indonesia - Wahyu Widiana (Al-Ulum, 2010)
This paper answers the difference between hizab and rukyat system in Indonesia. When there is a difference, the public at large directly "alleges" that the difference was due to the difference between hizab and rukyat. It is true that the differences can be caused by the difference method. However, in many cases, the dispute was not merely caused by the two types. It is very often that it occurred because of the differences among its own expert reckoning, or the differences among internal rukyat expert, or other outside technical differences hizab and rukyat. Generally speaking, Indonesian government policy is to involve all stakeholders in setting the early months of qomariyah.